A Course in Mathematical Cryptography - Baumslag, Gilbert; Baumslag, Gilbert; Fine, Benjamin 1948-; Kreuzer, Martin; Rosenberger, Gerhard (De Gruyter, 2015)
The subject of this book is mathematical cryptography. By this we mean the mathematics involved in cryptographic protocols. As the field has expanded, using both commutative and noncommutative algebraic objects as cryptographic platforms, a book describing and explaining all these mathematical methods is of immeasurable value. Gilbert Baumslag?; Benjamin Fine, Fairfield Uni;Martin Kreuzer, Uni of Passau; Gerhard Rosenberger, Uni of Hamburg.- Resumé vydavatel
Lizenzpflichtig
Keywords: kódování; kryptografie; matematika; coding; cryptography; mathematics; elektronické knihy; učebnice; electronic books; textbooks